الشيخ الفضيل الورتلاني ودوره الفكري والإصلاحي بالجزائر وفرنسا (1931م_1959م) - زرارة, علي (University of Eloued جامعة الوادي, 2020)
يعتبر الشيخ الفضيل الورتلاني من بين الشخصيات الإصلاحية التي عرفتها الجزائر خلال النصف الأول من القرن العشرين،حيث استطاع الشيخ الفضيل الورتلاني بناءا على تكوينه الديني واعتمادا على مبادئه الفكرية والإصلاحية المستمدة من ملازمته لشيوخ جمعية العلماء المسلمين العمل على نشر الأفكار التوعوية ذات البعد الإصلاحي في جانبه الديني و الاجتماعي وحتى السياسي داخل الجزائر وخارجها, مثلما كان الحال بفرنسا, وذلك من خلال نشره للعديد من المقالات في الكثير من الصحف وإلقائه للعديد من الخطب الهادفة لإصلاح المجتمع, وتكوين جيل ذو وعي ديني وسياسي يمكنه من مجابهة الأساليب الاستعمارية الرامية إلى طمس مقومات الشخصية العربية الإسلامية. Abstract: El sheikh el fodil El ouartalani is considered one of the personality who brought reforms to Algeria during the first half of the 20th century, he was able to build from his religious training and based on his Sensitization ideas and his reforms brought back from the teachers of the association of Algerian Muslim scholars, he worked on the publication of awareness-raising ideas which have a distant goal aiming at the side and social and even political reform inside Algeria and outside as was the case in France, where he published articles in several newspapers. he also made speeches aimed at social reform as well as the formation of a generation that can acquire a religious awareness and political which will allow him to confront the means of colonialization to eliminate the principles of the Arab and Muslim characters
كقال
Keywords: الكلمات المفتاحية: الفضيل الورتلاني,الافكار,الإصلاح,الوعي,الوطنية ,الجزائر ,فرنسا. ; key words: el fodil El ouartalani- ideas- The Reformation- Sensitization- national- Algerie -la france